PERBEDAAN PENGARUH ABDOMINAL STRECHING EXERCISE DENGAN KOMPRES HANGAT TERHADAP PENURUNAN NYERI HAID (DISMENORHEA) PADA MAHASISWI FISIOTERAPI STIKES SITI HAJAR MEDAN TAHUN 2018 - Dewi Agustina (Akademi Kebidanan Ika Bina, 2019)
Dysmenorrhea is menstrual pain in the lower abdomen that is cramped in the lower abdomen felt during menstruation so that it can interfere with the learning process of student learning activities. Efforts to reduce menstrual pain can be done with Abdoninal Exercise Exercise exercises and warm compresses. Of the 30 Siti Hajar STIKes students in Medan, 7 of them said that the effort to handle dysmenorrhea was done by applying eucalyptus oil, resting, 5 people taking analgesic medicine and 6 people using warm compresses and some not handling. This study aims to determine the differences in the effect of abdominal stretching exercises with warm compresses on decreasing menstrual pain (dismenorrhea) in STIKes Siti Hajar Medan students. This study uses a type of quasi experimental research, with two group pre and post design research designs. The sampling technique uses simple random sampling. The number of samples is 30 female students. The first group given warm compresses is done on the first day of menstruation until day 3 for 20 minutes is done for 2x the menstrual period and the second group is given abdominal streching training which is an abdominal stretching exercise performed with a duration of 10 minutes for 60 days performed 3 times a week. Pain measurement using the Visual Analogue Scale (VAS). Test hypotheses with univariate and bivariate analysis and different influence tests using independent t test. The results showed that students experienced menstrual pain before being given abdominal streching exercise exercises, namely 53.3% experienced moderate pain decreased after intervention 20% moderate pain and menstrual pain before being given warm compresses which was 46.7% experienced mild pain and after the intervention had decreased pain medium 26.7%. The mean pre test 3.6 decreased significantly to 2.8 (post test) with a value of p = 0.011 in abdominal stretching exercise. The mean pre test 3.5 did not experience a significant decrease of 3.3 (post test) with a value of p = 0.429 for giving warm compresses. It is recommended that the STIKes Education Institute Siti Hajar Medan include abdominal streching exercise training material for students as a learning to reduce menstrual pain and students use regular abdominal exercise training for 3 weeks to reduce menstrual pain. The output plan of this study is scientific publications in national journals (ISSN). Then the Abdominal Streching Exercise and Warm Compress Module in dealing with menstrual pain. Keywords: Menstrual Pain, Abdominal Streching Exercise, Warm Compress